INTELLIGENT POWER MODULE CONTROLLED BY MICROCOMPUTER AND IMPLEMENTED IN AC MOTOR SPEED REGULATOR (ETIMA, 2024)
In the paper, a V/f AC motor speed regulator based on an intelligent power module (IPM) and a microcomputer is designed and practically implemented. The ATmega 328P microcomputer controls the operation of the IPM TM 35 and generates the SPWM pulses for controlling an asynchronous 3 phase AC motor. The intelligent power module TM 35 works as a power driver that isolates and transmits the SPWM signals from the microcomputer to the AC motor. A basic goal in the design of the device is the reduction of the necessary hardware components and the price, as well as the improvement of the reliability of operation. The control and visualization of the operation modes of the V/f controller is realized with an LCD display. The operation of the controller at idle and under load has been tested.